A general strategy for the synthesis of α-trifluoromethyl- and α-perfluoroalkyl-β-lactams via palladium-catalyzed carbonylation. Issue 31 (12th July 2021) - Li, Yang; Zhang, Cai-Lin; Huang, Wei-Heng; Sun, Ning; Hao, Meng; Neumann, Helfried; Beller, Matthias
Abstract : β-Lactam compounds play a key role in medicinal chemistry, specifically as the most important class of antibiotics. Abstract : β-Lactam compounds play a key role in medicinal chemistry, specifically as the most important class of antibiotics. Here, we report a novel one-step approach for the synthesis of α-(trifluoromethyl)-β-lactams and related products from fluorinated olefins, anilines and CO. Utilization of an advanced palladium catalyst system with the Ruphos ligand allows for selective cycloaminocarbonylations to give diverse fluorinated β-lactams in high yields.